2014
DOI: 10.1007/s12298-014-0249-z
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in photochemical efficiency of photosystem II in wheat plant on hot summer day

Abstract: In this study the effect of increasing temperature on photochemical efficiency of PS II in wheat plants has been studied on a hot summer day (9:00 AM (Control)-7:00 PM) by measuring Chl a fluorescence. Increasing temperature for a short period of time (2-4 h), in nature affects the efficiency of PS II complex reversibly and does not cause permanent damage to any of the components of photosystem II. A scheme has been provided to demonstrate the sequence and severity of events which get affected maximum by tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 25 publications
1
18
1
Order By: Relevance
“…We hypothesized that photosynthesis and pollen viability under heat treatment are negatively impacted. Although changes in photosystem‐II efficiency have been associated with grain yield (Ort et al , ; Sanchez‐Bragado et al , ; Lin et al , ), as well as with responses to heat (Mathur and Jajoo, ; Yamamoto, ), we did not find statistically significant evidence that photosystem‐II efficiency was affected by heat. Similarly, we did not find statistically significant changes in pollen viability, despite pollen viability having been reported to be affected by heat in other species (Schoper et al , ; Vara Prasad et al , ; Kumar et al , ; Jiang et al , ), as well as in quinoa (Hinojosa, Matanguihan, et al , ).…”
Section: Resultscontrasting
confidence: 82%
“…We hypothesized that photosynthesis and pollen viability under heat treatment are negatively impacted. Although changes in photosystem‐II efficiency have been associated with grain yield (Ort et al , ; Sanchez‐Bragado et al , ; Lin et al , ), as well as with responses to heat (Mathur and Jajoo, ; Yamamoto, ), we did not find statistically significant evidence that photosystem‐II efficiency was affected by heat. Similarly, we did not find statistically significant changes in pollen viability, despite pollen viability having been reported to be affected by heat in other species (Schoper et al , ; Vara Prasad et al , ; Kumar et al , ; Jiang et al , ), as well as in quinoa (Hinojosa, Matanguihan, et al , ).…”
Section: Resultscontrasting
confidence: 82%
“…The disappearance of the K step after 72 h may indicate restoration of OEC function, which we attribute to prior acclimation of C. saccharophila to environmental factors to which it was exposed. Similar observation has been reported by Mathur and Jajoo () in wheat plants, where the K step appeared upon increased day temperature, but was diminished with time after continuous exposure of plants to sunlight. The thermostability of OEC in high temperature stress plants has been reported previously by Wang et al .…”
Section: Resultssupporting
confidence: 90%
“…It has been shown that salt stress reduces photosynthetic activities in plants via the inhibition of photosystem II complex (PSII) at both acceptor [QA] and donor sides (oxygen-evolving complex OEC), and destruction of chlorophyll pigments by the accumulation of toxic ions (Chen and Murata 2011; Shu et al 2012). The reduction observed in F v /F m may be associated with damage to the PSII reaction center (Kadir et al 2007) and the decrease in the quantum efficiency of PSII photochemistry (Mathur and Jajoo 2014). The dissipation energy ( DIo / RC ) and electron flux ( ETo/RC ) per active reaction center increased during salt stress, due to the increased proportion of the inactive reaction centers in the leaves exposed to salt stress (Mehta et al 2011), resulting in the ineffective exploitation of light energy received in the inactivated reaction centers (Satoh et al 1983).…”
Section: Discussionmentioning
confidence: 99%